2022
DOI: 10.1186/s12936-022-04220-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mosquito properties of Pelargonium roseum (Geraniaceae) and Juniperus virginiana (Cupressaceae) essential oils against dominant malaria vectors in Africa

Abstract: Background More than 90% of malaria cases occur in Africa where the disease is transmitted by Anopheles gambiae and Anopheles arabiensis. This study evaluated the anti-mosquito properties of Juniperus virginiana (JVO) and Pelargonium roseum (PRO) essential oils (EOs) against larvae and adults of An. gambiae sensu lato (s.l.) from East Africa in laboratory and semi-field conditions. Methods EOs was extracted from the aerial green parts of Asian herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Different strategies have been explored to prevent the transmission of mosquito-borne diseases: targeting the vector (Niang et al, 2018), and the use of larvicides, insecticides, and repellants (Derua et al, 2018;Derua et al, 2019). Natural products have been investigated for larvicidal, insecticidal, and repellant activities due to their environmental safety, nontoxicity, specificity, and lack of damage to valuable natural insects (Yohana et al, 2022). In this study, phytochemical screening of the two plants revealed the presence of secondary plant metabolites as shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Different strategies have been explored to prevent the transmission of mosquito-borne diseases: targeting the vector (Niang et al, 2018), and the use of larvicides, insecticides, and repellants (Derua et al, 2018;Derua et al, 2019). Natural products have been investigated for larvicidal, insecticidal, and repellant activities due to their environmental safety, nontoxicity, specificity, and lack of damage to valuable natural insects (Yohana et al, 2022). In this study, phytochemical screening of the two plants revealed the presence of secondary plant metabolites as shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Given these facts, mosquitoes control agents from natural sources can be considered as safe and effective alternatives. Several studies introduced mosquito repellent and larvicidal activity of some extracts and essential oils of plants ( 7 – 11 , 21 22 ). According to these studies, the products of traditional medicine have the potential to be used successfully in mosquito control programs.…”
Section: Discussionmentioning
confidence: 99%
“…Larvicides, pupicides and ovicides treatments can also help to control transmission parameters ( 7 – 11 , 21 22 ). A larvicide is a type of insecticide that effects on the larval life stage of an insect and consequently, reduces the adult mosquito population in breeding areas.…”
Section: Discussionmentioning
confidence: 99%
“…Besides secondary metabolites of plants, essential oils from plant based origin are considered to be good mosquitocidal agent (Senthil-Nathan 2020;Yohana et al 2022). Essential oils obtained from aromatic plants, namely Monodora myristica, Xylopia aethiopica, Aframomum citratum (Nkuimi Wandjou et al 2022), medicinal plants Cymbopogon nardus, Eucalyptus globulus, Mentha arvensis, Citrus limon and Trachyspermum ammi (Kamaraj et al 2023), weeds Mikania scandens (Radhakrishnan et al 2023).…”
Section: Essential Oils As Vector Control Agentmentioning
confidence: 99%
“…Besides secondary metabolites of plants, essential oils from plant based origin are considered to be good mosquitocidal agent (Senthil‐Nathan 2020; Yohana et al . 2022). Essential oils obtained from aromatic plants, namely Monodora myristica , Xylopia aethiopica , Aframomum citratum (Nkuimi Wandjou et al .…”
Section: Essential Oils As Vector Control Agentmentioning
confidence: 99%